Environment Keeper in Arabic Short Story: a Perspective of Ecocritical Theory - Asrori, Hadi; Sartini, Ni Wayan; Muniroh , Saidah; Abyad, Habil; Sa’diyah, Halimatus; Adam, Faisal Mahmoud (Al-Ma‘rifah, 2025)
Parents play a crucial role in fostering children’s empathy and care for nature. However, in the modern era, these values are often neglected, leading to future behaviors such as indifference toward environmental destruction, improper waste disposal, and the exploitation of natural resources. Literary ecocriticism offers an alternative solution through children’s literature as a medium to instill ecological awareness. This study aims to explore forms of children’s sensitivity to nature in the short story Aṭfāl al-Ghābah by Muḥammad ‘Aṭīyah al-‘Ibrāshī, analyzed from a literary ecocritical perspective. A descriptive qualitative method was employed, with data collected through reading and note-taking, then analyzed in three stages: data reduction, data display, and conclusion drawing. The findings indicate that children’s awareness is reflected in behaviors such as obeying the deer’s advice, avoiding harm to animals, rejecting exploitation, expressing joy in the forest’s beauty, feeling sadness upon leaving it, and demonstrating awareness of forest preservation. This study suggests that children’s literature can be an effective medium for environmental education, helping to foster a generation that respects and protects nature.